Can malaria parasite pathogenesis be prevented by treatment with tumor necrosis factor-alpha? - Avner Friedman; Edward M. Lungu (Mathematical Biosciences and Engineering)
We consider a model incorporating the influence of innate and adaptive immune responses on malaria pathogenesis. By calculating the model reproduction number for a special representation of cytokine interaction, we have shown that the cytokine tumour necrosis factor-$α$ can be administered to inhibit malaria infection. We have also found that if the cytokine $F^*$ and a generic drug of efficacy $ε$ are administered as dual therapy then clearance of the parasite can be achieved even for a generic drug of low efficacy. Our study is recommending administration of dual therapy as a strategy to prevent parasites from developing resistance to malaria treatment drugs.